BRAF V600E Mutation Is Associated with mTOR Signaling Activation in Glioneuronal Tumors. (11th September 2013) - Prabowo, Avanita S.; Iyer, Anand M.; Veersema, Tim J.; Anink, Jasper J.; Schouten‐van Meeteren, Antoinette Y. N.; Spliet, Wim G. M.; van, Pieter C.; Ferrier, Cyrille H.; Capper, David; Thom, Maria; Aronica, Eleonora
Abstract BRAF V600E mutations have been recently reported in glioneuronal tumors (GNTs). To evaluate the expression of the BRAF V600E mutated protein and its association with activation of the mammalian target of rapamycin (mTOR) pathway, immunophenotype and clinical characteristics in GNTs, we investigated a cohort of 174 GNTs. The presence of BRAF V600E mutations was detected by direct DNA sequencing and BRAF V600E immunohistochemical detection. Expression of BRAF‐mutated protein was detected in 38/93 (40.8%) gangliogliomas (GGs), 2/4 (50%) desmoplastic infantile gangliogliomas (DIGs) and 23/77 (29.8%) dysembryoplastic neuroepithelial tumors (DNTs) by immunohistochemistry. In both GGs and DNTs, the presence of BRAF V600E mutation was significantly associated with the expression of CD34, phosphorylated ribosomal S6 protein (pS6; marker of mTOR pathway activation) in dysplastic neurons and synaptophysin (P < 0.05). In GGs, the presence of lymphocytic cuffs was more frequent in BRAF‐mutated cases (31 vs. 15.8%; P = 0.001). The expression of both BRAF V600E and pS6 was associated with a worse postoperative seizure outcome in GNT (P < 0.001). Immunohistochemical detection of BRAF V600E‐mutated protein may be valuable in the diagnostic evaluation of these glioneuronal lesions and the observed association with mTOR activation may aid in the development of targeted treatment involving specific pathogenic pathways.